2020
DOI: 10.1038/s41416-020-01156-1
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine metabolic circuitries: druggable targets in cancer

Abstract: To enable survival in adverse conditions, cancer cells undergo global metabolic adaptations. The amino acid cysteine actively contributes to cancer metabolic remodelling on three different levels: first, in its free form, in redox control, as a component of the antioxidant glutathione or its involvement in protein s-cysteinylation, a reversible post-translational modification; second, as a substrate for the production of hydrogen sulphide (H2S), which feeds the mitochondrial electron transfer chain and mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 244 publications
(293 reference statements)
0
111
0
2
Order By: Relevance
“…Cancer cells mainly depend on exogenous cysteine upregulating the system xc--mediated import of cystine in exchange for glutamate [141]. Serine is a primary feeder of one-carbon metabolism in cancer, sustaining purine and thymidylate biosynthesis.…”
Section: Box 2-key Amino Acids In Cancer Metabolismmentioning
confidence: 99%
“…Cancer cells mainly depend on exogenous cysteine upregulating the system xc--mediated import of cystine in exchange for glutamate [141]. Serine is a primary feeder of one-carbon metabolism in cancer, sustaining purine and thymidylate biosynthesis.…”
Section: Box 2-key Amino Acids In Cancer Metabolismmentioning
confidence: 99%
“…Neighboring stromal cells characterized by BMSCs can take up cystine via system Xc(-) and release cysteine [ 31 ]. A vast majority of cells, including tumor cells, do not depend on extracellular cysteine for GSH synthesis [ 31 , 35 , 36 ]. Instead, they take up cystine (two cysteine molecules joined by a disulfide bond), the more abundant and more stable oxidized form, and reduce it to cysteine in the cytoplasm [ 37 ].…”
Section: Xct (Slc7a11)mentioning
confidence: 99%
“…In fact, we have previously shown that CIH changes the dynamics of cysteine pool to an oxidative status in the kidney when HTN is established [ 7 ]. Cysteine (Cys) is the predominating thiol in extracellular fluids [ 12 , 13 ] and its availability is a net contribution of three pools which can dynamically exchange one-to-one depending on the redox status of the tissue involved [ 7 , 14 , 15 , 16 ]. The protein-bound fraction ( S -cysteinylated proteins, CysSSP) is generated by a reversible post-translational modification through a disulfide bond [ 14 ].…”
Section: Introductionmentioning
confidence: 99%